Improvement in Patients’ Ability to Care for Anxiety and Impaired Body Image: A Case Report of Acceptance and Commitment Therapy and Family Psychoeducation - Rasmawati Rasmawati; Budi Anna Keliat; Herni Susanti (Jurnal Keperawatan Indonesia, 2020)
Heart failure and hypertension are non-communicable diseases that are responsible for 70% of deaths worldwide and cause anxiety and impaired body image. Nursing interventions (therapy in general) and acceptance and commitment therapy increase patients’ acceptance of the disease and commitment to alleviate anxiety and improve impaired body image. Meanwhile, family psychoeducation improves the family’s ability to care for the patient. This case report presents two patients with heart failure and hypertension. The two patients experienced a decrease in symptoms on the cognitive aspects (difficulty concentrating, focusing on self, and decline body changes), affective aspects (worry, shame, and despair), physiological aspects (sleep disorders and appetite), and behavioral aspects (daydreaming, decreased productivity, and social difficulties). Patients who find difficulty enjoying daily activities and increasing their ability and commitment to overcome anxiety and impaired body image should receive nursing intervention, acceptance and commitment therapy, and family psychoeducation as part of nursing services. Abstrak Peningkatan Kemampuan Klien Merawat Ansietas dan Gangguan Citra Tubuh: Laporan Kasus Acceptance and Commitment Therapy dan Psikoedukasi Keluarga. Gagal jantung dan hipertensi merupakan penyakit tidak menular yang menjadi penyebab 70% kematian di dunia serta menyebabkan ansietas dan gangguan citra tubuh. Tindakan keperawatan ners dan ners spesialis Acceptance and commitment therapy diberikan pada klien agar dapat meningkatkan penerimaan terhadap penyakit dan komitmen merawat ansetas dan gangguan citra tubuh. Psikoedukasi keluarga dilakukan agar keluarga mampu membantu merawat klien dalam menghadapi penyakitnya. Metode yang digunakan berupa laporan kasus dalam bentuk case series pada dua klien dewasa dengan gagal jantung dan hipertensi. Hasil menunjukkan bahwa kedua klien mengalami penurunan gejala pada aspek kognitif berupa sulit konsentrasi, fokus pada diri sendiri, tidak menerima perubahan tubuh; afektif: khawatir, malu dan putus asa; aspek fisilogis: gangguan tidur dan tidak nafsu makan; perilaku: melamun, penurunan produktivitas; dan sosial: sulit menikmati kegiatan harian serta terjadi peningkatan kemampuan klien dalam menerima penyakit dan komitmen merawat ansietas dan gangguan citra tubuh. Pemberian tindakan keperawatan ners dan ners spesialis acceptance and commitment therapy serta psikoedukasi keluarga perlu dibudayakan dalam pemberian pelayanan keperawatan di unit umum. Kata Kunci: acceptance and commitment therapy, ansietas, gangguan citra tubuh, hipertensi, psikoedukasi keluarga